Membangun Keadilan dan Komitmen Global dalam Kebijakan Iklim Nasional: Analisis Reinterpretasi CBDR-RC di Indonesia - Mardiyanto, Ibnu (Universitas Suryakancana, 2025)
AbstractThis study examines the interpretation and application of the principle of Common but Differentiated Responsibilities and Respective Capabilities (CBDR-RC) in Indonesia’s climate change policies within the international climate change law regime. The analysis focuses on how this principle is operationalized within the national legal framework to balance international obligations with the State’s domestic capacities. This research employs a normative legal method, drawing on statutory and conceptual approaches, through an analysis of relevant international legal instruments and Indonesia’s national climate policies. The findings demonstrate that the reinterpretation of the CBDR-RC principle provides a legal basis for Indonesia to adopt flexible and proportionate climate policies without compromising its obligation to contribute to global emission-reduction efforts. The application of this principle underscores the dimensions of distributive justice, sustainable development, and the protection of vulnerable groups, as reflected in the formulation of national climate policies, particularly through the Nationally Determined Contributions (NDC) mechanism. This study concludes that the CBDR-RC principle holds normative significance in strengthening the legal legitimacy of Indonesia’s position and in maintaining coherence between national law and international climate change law. AbstrakPenelitian ini menganalisis pemaknaan dan penerapan prinsip Common but Differentiated Responsibilities and Respective Capabilities (CBDR-RC) dalam kebijakan perubahan iklim Indonesia sebagai bagian dari rezim hukum perubahan iklim internasional. Fokus penelitian diarahkan pada bagaimana prinsip tersebut dioperasionalisasikan dalam kerangka hukum nasional untuk menyeimbangkan kewajiban internasional dengan kapasitas domestik negara. Penelitian ini menggunakan metode hukum normatif dengan pendekatan perundang-undangan dan konseptual, melalui analisis terhadap instrumen hukum internasional serta kebijakan iklim nasional Indonesia. Hasil penelitian menunjukkan bahwa reinterpretasi prinsip CBDR-RC berfungsi sebagai dasar yuridis bagi Indonesia untuk mengadopsi kebijakan iklim yang fleksibel dan proporsional, tanpa menegasikan kewajiban kontribusi terhadap tujuan global pengurangan emisi. Penerapan prinsip ini menegaskan dimensi keadilan distributif, keberlanjutan pembangunan, dan perlindungan kelompok rentan, yang tercermin dalam perumusan kebijakan iklim nasional, khususnya melalui mekanisme Nationally Determined Contributions (NDC). Penelitian ini menyimpulkan bahwa prinsip CBDR-RC memiliki signifikansi normatif dalam memperkuat legitimasi hukum posisi Indonesia serta menjaga konsistensi antara hukum nasional dan hukum perubahan iklim internasional.